The Value of Preventative Dental Care: A Discrete-Choice Experiment. (July 2021) - Boyers, D.; van der Pol, M.; Watson, V.; Lamont, T.; Goulao, B.; Ramsay, C.; Duncan, A.; Macpherson, L.; Clarkson, J.
Scale and polish (SP) and oral hygiene advice (OHA) are commonly provided in primary care dental practice to help prevent periodontal disease. These services are widely consumed by service users, incurring substantial cost, without any clear evidence of clinical benefit. This article aims to elicit general population preferences and willingness to pay (WTP) for preventative dental care services and outcomes. An online discrete-choice experiment (DCE) was completed by a nationally representative sample of the UK general population. Respondents each answered 10 choice tasks that varied in terms of service attributes (SP, OHA, and provider of care), outcomes (bleeding gums and aesthetics), and cost. Choice tasks were selected using a pivoted segmented experimental design to improve task realism. An error components panel logit model was used to analyze the data. Marginal WTP (mWTP) for each attribute and level was calculated. In total, 667 respondents completed the DCE. Respondents valued more frequent SP, care provided by a dentist, and personalized OHA. Respondents were willing to pay for dental packages that generated less frequent ("never" or "hardly ever") bleeding on brushing and teeth that look and feel at least "moderately clean." Respondents were willing to pay more (+£145/y) for improvements in an aesthetic outcome from "very unclean" (−£85/y) to "very clean" (+£60/y) than they were for reduced bleeding frequency (+£100/y) from "very often" (−£54/y) to "never" (+£36/y). The general population value routinely provided SP, even in the absence of reductions in bleeding on brushing. Dental care service providers must consider service user preferences, including preferences for both health and nonhealth outcomes, as a key factor in any service redesign. Furthermore, the results provide mWTP estimates that can be used in cost-benefit analysis of these dental care services.